Numerical Simulations of Scaling of the Chamber Dimensions of the Liquid Piston Compressor for Hydrogen Applications - Marina Konuhova; Valerijs Bezrukovs; Vladislavs Bezrukovs; Deniss Bezrukovs; Maksym Buryi; Nikita Gorbunovs; Anatoli I. Popov (Technologies)
Hydrogen compression is a critical process in hydrogen storage and distribution, particularly for energy infrastructure and transportation. As hydrogen technologies expand beyond limited industrial applications, they are increasingly supporting the green economy, including offshore energy systems, smart ports, and sustainable marine industries. Efficient compression technologies are essential for ensuring reliable hydrogen storage and distribution across these sectors. This study focuses on optimizing hydrogen compression using a Liquid Piston Hydrogen Compressor through numerical simulations and scaling analysis. The research examines the influence of compression chamber geometry, including variations in radius and height, on thermal behavior and energy efficiency. A computational model was developed using COMSOL Multiphysics® 6.0, incorporating Computational Fluid Dynamics (CFD) and heat transfer modules to analyze thermodynamic processes. The results highlight temperature distribution in hydrogen, working fluid, and chamber walls at different initial pressures (3.0 MPa and 20.0 MPa) and compression stroke durations. Larger chamber volumes lead to higher temperature increases but reach thermal stabilization. Increasing the chamber volume allows for a significant increase in the performance of the hydraulic compression system with a moderate increase in the temperature of hydrogen. These findings provide insights into optimizing hydrogen compression for enhanced production and broader applications.